Black swan theory: legal policy of the Indonesian national healthcare - Budiono, Arief; Absori, Absori; Ngestiningrum, Ayesha Hendriana; Dewi, Elya Kusuma; Nurhayati, Nunik; Arum Prastyanti, Rina; Ibrahim, Alisa (Legality : Jurnal Ilmiah Hukum, 2022)
The Indonesian National Health Service (NHS) is part of Indonesia’s national social security system. Its implementation is full of problems, such as the rejection of patients, the NHS payment which is lower than the real health cost, sanctions, fines, etc. The Indonesian National Social Security System, especially the NHS services, was established by the state to give social protection to its citizens. The Black Swan Theory is based on the presumption that all swans are white, thus in this case, the Indonesian NHS is truly a program aimed to give social security in the health sector, just as the general conditions of social securities applied in other countries. This research studies this theory to explore the paradoxes which happen in the Indonesian NHS to find the black swan. In this case, the black swan is a paradoxical symbol regarding the regulations and the problems of the Indonesian NHS. This research uses the juridical-doctrinal or the normative method and is descriptive research with a qualitative approach. Based on the Black Swan theory, this research tries to find paradoxical, extreme, and unpredictable discrepancies in the Indonesian NHS. It is found that the Indonesian NHS is a black swan or unpredicted according to black swan theory. The objectives, practices, and regulations of this NHS are truly different from the NHS which is supposed to be given to the Indonesians. It transfers the government’s burden in establishing the health service and the rights of the citizens to the citizens, coupled with the threat of sanctions which is unknown in NHS. The applied Indonesian NHS has an extensive impact on hundreds of millions of Indonesian citizens.